A New ?-conjugated 1,7-diphenoxy-perylene bisimide: Synthesis, characterization, photophysical and electrochemical properties - Pakseresht, Mayram; Bodapati, Jagadeesh B.; Icil, Huriye (Elsevier Science Sa, 2018)
A novel pi-conjugated 1,7-diphenoxy-perylene bisimide (perylene diimides, PDIs) (4) was synthesized starting from 1,7(6)-diphenoxyperylene-3,4,9,10-tetracarboxylic bisanhydride (3). N,N'-bis(4-hydroxyphenyl)-perylene-3,4,9,10-tetracarboxy bisimide (1) was synthesized and characterized also for the comparison between a non-bay substituted symmetrical perylene diimide and the bay substituted symmetrical perylene diimide with the same substituents at the PDI imide positions. Positive and weak solvatochromic effect for the compounds 3 and 4 was apparently observed in polar media. The absolute positions of LUMO and HOMO values of 1 and 3 in solution were -3.775 eV/- 6.035 eV and -3.971 eV/- 6.041, respectively. The HOMO, LUMO and E-g values for the compound 4 were not calculated due to the non-resolved reduction peaks most probably due to aggregation.
Keywords: Bay-; substituted perylene diimides; Optical properties; Electrochemistry; Low band gap